2018
DOI: 10.3991/ijet.v13i08.8291
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multimedia in Education for Special Education (MESE) to Improve Reading Ability and Memorizing for Children with Intellectual Disability

Abstract: The difference between learning using one sensory ability (e.g. reading text or hearing or looking at the pictures only) and two or more (e.g. reading text equipped by sound and visualized by animation; and even allows children to get involved directly in the process of learning) was that the low ability in memorizing. MESE (Multimedia in Education for Special Education) was a multimedia application developed for reading for children with intellectual disability. This research aimed to find out MESE effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…They also tended to have positive behavior towards new technology. This was supported by previous study that proved technology implementation could help potential that students had [17], including people with disabilities [18][19][20].…”
Section: Resultssupporting
confidence: 65%
“…They also tended to have positive behavior towards new technology. This was supported by previous study that proved technology implementation could help potential that students had [17], including people with disabilities [18][19][20].…”
Section: Resultssupporting
confidence: 65%
“…The significant increase in technique score across time within the intervention group shows that the multimedia visualization of a simplified 5‐step handwashing technique is effective in enabling students with MID to learn proper hand‐washing procedures. Munir, Wawan, Eddy Prasetyo, Jajang, and Aji Prasetya (2018) reported that the learning by using multimedia application enhanced reading skill and memorizing among children with special needs as it was attractive and had interactive capability that provided opportunity for them to learn independently. It is also easier and quicker for children with special needs in the intervention group to learn and memorize the simplified 5‐step handwashing technique than the conventional 7‐step technique in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…New media technology has brought about adequate steps required to ease the flow and understanding of language learning for individuals with learning disabilities. With MESE (Multimedia in Education for Special Education) applications leading to enhanced reading skills and memorization (Munir et al, 2018), and new media applications aiming to integrate reading fluency and automated word recognition facilities (Leon et al, 2017), new media shows promise in ameliorating ease of access and usability to its target populations. Additionally, one's self efficacy greatly determines their receptivity to learning a language, and researches have indicated that multimedia applications contribute to a hike in this construct within individuals with dyslexia (Osman et al, 2014).…”
Section: Identified Trends Following the Second Objectivementioning
confidence: 99%